Oxalate, inflammasome, and progression of kidney disease. Issue 4 (July 2016) - Ermer, Theresa; Eckardt, Kai-Uwe; Aronson, Peter S.; Knauf, Felix
Abstract : Purpose of review: Oxalate is an end product of metabolism excreted via the kidney. Excess urinary oxalate, whether from primary or enteric hyperoxaluria, can lead to oxalate deposition in the kidney. Oxalate crystals are associated with renal inflammation, fibrosis, and progressive renal failure. It has long been known that as the glomerular filtration rate becomes reduced in chronic kidney disease (CKD), there is striking elevation of plasma oxalate. Taken together, these findings raise the possibility that elevation of plasma oxalate in CKD may promote renal inflammation and more rapid progression of CKD independent of primary cause. Recent findings: The inflammasome has recently been identified to play a critical role in oxalate-induced renal inflammation. Oxalate crystals have been shown to activate the NOD-like receptor family, pyrin domain containing 3 inflammasome (also known as NALP3, NLRP3, or cryopyrin), resulting in release of IL-1β and macrophage infiltration. Deletion of inflammasome proteins in mice protects from oxalate-induced renal inflammation and progressive renal failure. Summary: The findings reviewed in this article expand our understanding of the relevance of elevated plasma oxalate levels leading to inflammasome activation. We propose that inhibiting oxalate-induced inflammasome activation, or lowering plasma oxalate, may prevent or mitigate progressive renal damage in CKD, and warrants clinical trials.